Development and performances of a 0.5 kW high-pressure alkaline water electrolyser. (12th November 2019) - Kuleshov, N.V.; Kuleshov, V.N.; Dovbysh, S.A.; Grigoriev, S.A.; Kurochkin, S.V.; Millet, P.
Abstract: The purpose of this research paper is to describe the characteristics and electrochemical performances of a pressurized alkaline water electrolysis short stack (5-cells, 0.5 kW) operated at 80 °C, from atmospheric pressure up to 100 bars. Expanded grids of metallic nickel covered with specific porous catalytic structures have been used as working electrodes. A polysulfone-based diaphragm with a high ionic conductivity has been specifically designed for operation in pressurized alkaline water electrolysis cells. I–V polarization curves have been recorded at current densities up to 1000 mA/cm 2, at temperatures up to 80 °C and under pressures up to 100 bars. The water electrolysis efficiency of this short-stack has been determined. A specific energy consumption of ca. 4.4–4.5 kWh/Nm 3 has been obtained in the high current density range. Durability tests have been performed on the short stack over 1000 h. A limited degradation rate <5 μV/h has been recorded over that period of test. Highlights: Expanded nickel grids with catalysts coatings were optimized for the HER and OER. Thin porous polysulfone diaphragms containing TiO2 fillers were used as separator. A 0.5 kW alkaline water electrolysis short-stack was developed and tested. Current densities up to 1 A/cm 2 and pressures up to 100 bars were achieved.